Kemampuan Literasi Baca-Tulis Dan Literasi Digital Calon Guru Sekolah Dasar - Deti Indah Kiranti; Dwi Octaviani Putri; Cici Isnawati; Septi Sulistyorini; Riska Riska; Sofyan Iskandar; Nuur Wachid Abdul Majid; Neneng Sri Wulan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The research conducted aims to determine the extent of literacy and digital literacy of prospective elementary school teacher at one of the tertiary institutions in Purwakarta Regency. This research was conducted because it saw how big the teacher’s role was in the success of teaching and learning in the schools. Quality learning activities, of course, require the ability of educators and prospective educators who are competent. Through qualified teachers, students literacy skills in the future will be realized as expected. This study used data collections techniques by distributing questionnaires containing questions regarding understanding the concepts of literacy and digital literacy, as one of the competencies that prospective elementary school teachers must possess. The results of the questionnaire were filled out by a sample of 52 respondents, and it was proven by the fact on the ground that prospective elementary school teacher students were able to implement creative learning simulations so as to create interactive learning conditions with students inside and outside the classroom.